2022
DOI: 10.3389/fcimb.2022.812345
|View full text |Cite
|
Sign up to set email alerts
|

The Oral, Gut Microbiota and Cardiometabolic Health of Indigenous Orang Asli Communities

Abstract: The Orang Asli (OA) of Malaysia have been relatively understudied where little is known about their oral and gut microbiomes. As human health is closely intertwined with the human microbiome, this study first assessed the cardiometabolic health in four OA communities ranging from urban, rural to semi-nomadic hunter-gatherers. The urban Temuan suffered from poorer cardiometabolic health while rural OA communities were undergoing epidemiological transition. The oral microbiota of the OA were characterised by seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…Under the same geopolitical boundaries, hunter-gatherer Jehai and agricultural Temiar have similar microbial taxa abundance (Fig. 3), similar results as suggested by the previous study 72 , and show distinctness from the African and North American hunter-gatherers (Fig. 6B).…”
Section: Moving Beyond Generalizationsupporting
confidence: 85%
See 2 more Smart Citations
“…Under the same geopolitical boundaries, hunter-gatherer Jehai and agricultural Temiar have similar microbial taxa abundance (Fig. 3), similar results as suggested by the previous study 72 , and show distinctness from the African and North American hunter-gatherers (Fig. 6B).…”
Section: Moving Beyond Generalizationsupporting
confidence: 85%
“…This thing might be happened due to the different dietary practices. This assumption resolved by the previously published article 72 , the Temiar frequently consume rice, meat, sh, and plants that they grew such as sweet potato leaves which is more or less similar to the Jehai, on the contrary the Temuan consume a diet with lacking plant ber closely resembled urban Malaysians. The results also suggest that Jakun community of Malaysia exhibit high abundance of Prevotella within their gut microbial composition due to frequent consumption of 'Ulam' (a type of vegetable).…”
Section: Moving Beyond Generalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For that reason, the composition of the oral microbiota has been widely studied across different geographic areas and life stages and information on its taxonomy and ecology have been summarized and made freely accessible on the Human Oral Microbiome Database website (Dewhirst et al 2010 ) and the Oral Microbiome Bank of China database (Xian et al 2018 ). Nevertheless, it is undeniable that so far, oral microbiome studies have neglected populations from nonindustrialized countries: to date, there are only a few studies on African, Asian, or Indigenous cohorts (Yang et al 2019 , Nath et al 2021 , Yeo et al 2022 , Araújo et al 2023 ). Recent research has clearly shown that the oral bacterial community structures of healthy individuals is distinct from individuals suffering from diseases such as periodontitis, dental caries, oral cancer, IBDs, colonic cancer, and preterm birth (reviewed by Peng et al 2022 ).…”
Section: Oral Microbiotamentioning
confidence: 99%
“…These studies report that oral microbial diversity decreases with industrialization, with microbiome composition exhibiting differences based on lifestyle as well. More specifically, relative abundances of Neisseria , Haemophilus, Prevotella, and Streptococcus tend to decrease with industrialization [30, 31, 33, 35, 36]. However, several potential confounding factors may underlie the reported differences.…”
Section: Introductionmentioning
confidence: 99%